ANALYSIS AND VIBRATION REDUCTION STUDY OF ABNORMAL VIBRATION IN THE PIPELINE OF ULTRA-HIGH VOLTAGE CONVERTER STATION SYNCHRONOUS CONDENSER - WAN Yu; JIN Chuanling (Jixie qiangdu)
Abnormal vibration in the pipeline associated with large synchronous condensers not only reduces the lifespan of the pipeline but also affects the supply of the lubricating oil and coolant for the synchronous condenser, posing a serious risk of major safety accidents and jeopardizing the stability of the power system. The lubricating oil supply pipeline of a specific ultra-high voltage converter station synchronous condenser was taken as the research object. Multiple methods, including field measurements, fluid-structure coupling, and harmonic response analysis, were used to investigate the causes and mechanisms of the pipeline vibration. The results indicate that the periodic excitation force generated by the synchronous condenser itself is the main cause of pipeline vibration. Furthermore, a pipeline vibration reduction measure based on a tuned mass damper (TMD) was proposed. Experimental and simulation data shows that installing a TMD at the intermediate positions between suspension supports 4 and 5, as well as 6 and 7 in the lubricating oil supply pipeline system, yields the best vibration reduction effect. This approach can reduce the vibration acceleration of the pipeline system by over 90% and exhibits the excellent vibration reduction performance.